Microfinance - Torre, Mario La.; Vento, Gianfranco A.; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2006)
Microfinance is a comprehensive analysis of the operational, managerial and financial aspects of microfinance. The text provides a contemporary analysis of microfinance business covering the risks, returns and management issues associated with such activity. It analyzes the main products and services available in modern microfinance and explains how to manage the financial and non financial risks involved. The book also provides a performance and monitoring model for microfinance programmes and describes how microfinance can be regulated.
Keywords: Accounting; Banks and banking; Accounting/Auditing.; Banking